Let s breed adaptive taro - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The genetics and breeding of taro By A Ivancic & V Lebot, CIRAD, 2000. 195 pp. ISBN 2 87614 414 X FRF 230 E 35.05 For CIRAD s address details see elsewhere in this section